PRAGMATIC INTERPRETATION OF DIALECTISMS IN DIALOGIC TEXTS (American Journal of Research in Humanities and Social Sciences, 2023)
This article discusses the significance of dialectisms in enhancing the artistic and folkloric qualities of literary works. Various types of dialect-specific units, including phonetic, lexical, and grammatical dialectisms, are analyzed through dialogic texts. It is explored that in literary works, the pragmatic features of characters' speech are also influenced by dialect-specific lexicon, considered one of the fundamental linguistic units that reveal the relationships between interlocutors, serving as a means of speech individualization for characters and unveiling their internal, spiritual characteristics.